Effects of Different Pre-drying and Drying Methods on Volatile Compounds in the Pericarp and Kernel of Amomum tsao-ko - Qin, Hui-wei; Yang, Tian-mei; Yang, Shao-bing; Yang, Mei-quan; Wang, Yuan-zhong; Zhang, Jin-yu (Frontiers in Plant Science, 2022)
The effects of twelve different pre-drying and drying methods on the chemical composition in the pericarp and kernel of Amomum tsao-ko were studied. The volatile components were isolated from the samples by simultaneous distillation and extraction and analyzed by gas chromatography-mass spectrometry (GC-MS). Sixty and thirty-eight compounds were identified from pericarp and kernel, respectively, and the main constituents were oxygenated monoterpenes. These compounds were not only significantly affected by pre-drying and drying methods but also had different responses to processing methods due to different tissue locations. The oxygenated monoterpenes in pericarp and kernel were higher in pre-drying with boiling water (5 min) and sun-dried samples, respectively. Overall, the volatile components of pericarp were the highest under microwave drying (150 W), and the volatile components of kernel were the highest under sun drying. Additionally, the main components such as 1,8-cineole, 2-carene, (Z)-citral, nerolidol, (Z)-2-decenal, (E)-2-dodecenal, citral, (E)-2-octenal, 4-propylbenzaldehyde and phthalan showed remarkable variations in pre-drying and drying methods.